Articulatory-to-Acoustic Relations in Response to Speaking Rate and Loudness Manipulations. - Mefferd, Antje S.; Green, Jordan R. (Journal of Speech, Language & Hearing Research, 2010)
Purpose: In this investigation, the authors determined the strength of association between tongue kinematic and speech acoustics changes in response to speaking rate and loudness manipulations. Performance changes in the kinematic and acoustic domains were measured using two aspects of speech production presumably affecting speech clarity: phonetic specification and variability. Method: Tongue movements for the vowels /ia/ were recorded in 10 healthy adults during habitual, fast, slow, and loud speech using three-dimensional electromagnetic articulography. To determine articulatory-to-acoustic relations for phonetic specification, the authors correlated changes in lingual displacement with changes in acoustic vowel distance. To determine articulatory-to-acoustic relations for phonetic variability, the authors correlated changes in lingual movement variability with changes in formant movement variability. Results: A significant positive linear association was found for kinematic and acoustic specification but not for kinematic and acoustic variability. Several significant speaking task effects were also observed. Conclusion: Lingual displacement is a good predictor of acoustic vowel distance in healthy talkers. The weak association between kinematic and acoustic variability raises questions regarding the effects of articulatory variability on speech clarity and intelligibility, particularly in individuals with motor speech disorders. Reprinted by permission of the publisher.